International directory of company histories. Volume 172. - Johnson, Drew D.; Gale Group (Farmington Hills, Mich. St. James Press, a part of Gale, Cengage Learning, 2016)
Provides histories of companies that are a leading influence in a particular industry or geographic location. For students, job candidates, business executives, historians and investors.
24Hr HomeCare LLC -- Acrodea, Inc. -- Active Power, Inc. -- Agero, Inc. -- AmorePacific Corporation -- ANI Pharmaceuticals, Inc. -- Ashford University, LLC -- Asia World Company Limited -- Authentic Brands Group LLC -- AVX Corporation -- Azerbaijan Airlines CJSC -- Behavioural Insights Ltd. -- Blue Star Limited -- Brother Industries, Ltd. -- Bunkhouse Group, LLC -- CardCash.com -- The Carlyle Group L.P. -- Castlight Health, Inc. -- CBIZ, Inc. -- China General Nuclear Power Group -- Chromalox, Inc. -- CrossFit, Inc. -- Cuadrilla Resources Limited -- Sucocitrico Cutrale, Ltda. (dba Cutrale) -- CVB Financial Corporation -- Dentons -- Detroit Pistons Basketball Company -- Detroit Red Wings, Inc. -- Detroit Tigers, Inc. -- Dynamic Materials Corporation -- Evolent Health, LLC -- Fagor Electrodomesticos, S. Coop. Ltda. -- FFF Enterprises, Inc. -- General Motors UK Limited -- Global News Enterprises, LLC -- Hoss's Steak and Sea House Inc. -- ICA Gruppen AB -- Idaho Power Company -- Instacart -- Institute for Plastination -- International Monetary Fund -- Inuvo, Inv. -- J.D. Power and Associates -- J.J. Keller & Associates, Inc. -- Judicial Correction Services, Inc. -- Kenneth Cole Productions Inc. -- Les Enphants Co., Ltd. -- Marine Harvest ASA -- Mast Brothers LLC -- Millennial Media, Inc. -- Mississippi Lime Company -- MityLite, Inc. -- Moelis & Company -- The Monarch Cement Company -- Moonbat Co., Ltd. -- Nippon Coke & Engineering Company, Limited -- Novawax, Inc. -- Oberweis Dairy, Inc. -- Oberweis Dairy, Inc. -- OpSec Security Group plc -- Optimizely, Inc. -- Outdoor Research, LLC -- Pacific Maritime Association -- Patina Restaurant Group, LLC -- Pescanova, S.A. -- PetroKazakhstan, Inc. -- Petrossian Inc. -- Phillips Auctioneers LLC -- Proeza S.A. de C.V. -- PT Sinar Mas Multiartha Tbk -- Pure Flix Entertainment LLC -- Rock Island Arsenal-Joint Manufacturing and Technology Center -- Sentinel Offender Services, LLC -- The Slate Group LLC -- STAAR Surgical Company -- Stanadyne LLC -- Symphony Limited -- Tableau Software, Inc. -- TaskRabbit, Inc. -- The Joint Corp. -- Tiger Aspect Productions Ltd. -- Tilcon Connecticut Inc. -- Tiscali S.p.A. -- Tom Doherty Associates, LLC -- Torstar Corporation -- toupargel Groupe SA -- Tradeworx, Inc. -- Travelzoo Inc. -- Triple P N.V. -- Tubos de Acero de Mexico, S.A. (TenarisTamsa) -- UTV Software Communications Limited -- Vaillant Group GmbH -- Valence Surface Technologies -- Veeco Instruments Inc. -- Veolia Energy North America, LLC -- Vicente Sederberg, LLC -- Wagamama Limited -- Waxman Industries, Inc. -- Wealthfront Inc. -- Webber Oil Company -- Zotefoams plc.
Includes bibliographical references and indexes.
Keywords: Big business -- History -- Directories; Business enterprises -- History -- Directories; Corporations -- History -- Directories